The Emotional Dynamics of English Language Education Students Influence the Learning Process - Loka, Amanda Mayang Sandya; Sentana, Yuli Mahmudah (Universitas PGRI Adi Buana Surabaya, 2024)
This study aims to analyze how emotional dynamics, particularly heartbreak, affect the learning process of English Education students. The method used is mixed-method, with a sequential exploratory approach, where qualitative data is collected first through interviews with 5 students, then analyzed and continued with quantitative data collection through questionnaires filled out by 55 students. The results showed that heartbreak impacts on various aspects of learning, such as difficulty concentrating, decreased motivation to learn, lack of confidence, and delays in completing academic assignments. In addition, social pressure factors and lack of emotional support also worsen students' conditions. Thus, strategies are needed to help students manage their emotions in order to maintain learning effectiveness. This study confirms that emotional factors should not be ignored in the academic environment